Intelligent Cyber-Physical Modules for Monitoring Digital Protection of Production Facilities for Use in Emergency Situation - Chala, O.; Borodai, Y. (My University, 2026)
This paper highlights the intermediate results of research related to the development, design, and implementation of intelligent cyber-physical monitoring modules for digital protection of production facilities for use in emergencies. This allows for data processing directly on devices (at the "edge" of the network) to minimize delays in critical situations. The use of Digital Twins will ensure continuous synchronization of a physical object with its digital model for simulating emergency response scenarios without risk to real production. The research results provide insights into the initial aspects of designing and developing intelligent cyber-physical modules for monitoring digital protection in production for use in emergencies, which could be useful for researchers and developers in the fields of production automation, civil security, and emergency response robotics.
Інтелектуальні кіберфизичні модулі моніторингу цифрового захисту виробництв для застосування у надзвичайних ситуаціях
Keywords: cyber-physical systems; enterprise; protection, emergency; digital twins